Improving SOGI Asylum Adjudication: Putting Persecution Ahead of Identity. (19th July 2021) - Dustin, Moira; Ferreira, Nuno
Abstract: This article addresses the concern that decision-making in sexual orientation or gender identity (SOGI) asylum claims in Europe is often unfair, and that one way to remedy this is by improving the guidance provided to decision-makers when interpreting the Refugee Convention in respect of these claims. We begin by interrogating a number of different decision-making guidelines and models to assess whether they contribute to a fairer asylum system. We show that, for claims based on SOGI, success invariably depends on the decision-maker's assessment as to whether a claimant is, or would be perceived in their home country to be, a member of a SOGI minority, and so belongs to a Particular Social Group. Such focus risks neglecting analysis of the actual risk of persecution. We set out our own recommendation for a fairer approach based on prioritising SOGI-specific Country of Origin Information (COI) and the risk of persecution, rather than focusing on whether applicants are 'genuinely' members of a SOGI minority. We argue that this will lead to fairer outcomes that are less likely to be overturned on appeal and more consistent with the Refugee Convention's spirit and letter.